Motives for deliberate self-harm in a South African tertiary hospital - Van Zyl, Petrus Jasper Johannes (Department of Psychiatry and Mental Health, 2022)
Background: Although there is a growing body of literature on the epidemiology of deliberate self-harm (DSH) in South Africa, comparatively few studies have investigated the motives for self-harm. No studies have investigated the motives for DSH in Cape Town. Aim: To identify the range of motives for DSH in Cape Town, and how these motives are associated with different sociodemographic factors, the severity of self-injury, and levels of suicidal intent. Methods: Data were collected for 238 consecutive patients presenting with DSH to the emergency department of Groote Schuur Hospital in Cape Town, South Africa. The data were analysed using bivariate and multivariate analyses. Results: Patients engaged in DSH for a range of motives. Interpersonal issues was the most common motive (70%), followed by financial concerns (22%). Male patients were twice as likely as female patients to report interpersonal motives for their self-harm. Patients who reported interpersonal issues were more likely to engage in methods of DSH that involved damage to body tissue. Patients without tertiary education were more likely to report academic concerns as a motive, and patients who reported psychiatric illness as motive for DSH were more likely to require medical interventions than those who did not. Conclusion: This study contributes novel insights into the motives for DSH in the Cape Town context and provides the foundation for continued research on the subject. The study also gives impetus to the development of therapeutic interventions focused on the motives for self-harm.